Airman - Colfer, Eoin. (New York : Hyperion Books for Children, 2008)
In the 1890s on an island off the Irish coast, Conor Broekhart is falsely imprisoned and passes the solitary months by scratching designs of flying machines into the walls, including one for a glider with which he dreams of escape.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
5.8
5-8
Keywords: Flying-machines -- Juvenile fiction; Inventors -- Juvenile fiction; Islands -- Juvenile fiction; Prisoners -- Juvenile fiction; Adventure and adventurers -- Fiction; Flying machines -- Fiction; Historical fiction; Inventors -- Fiction; Islands -- Fiction; Prisoners -- Fiction; Adventure fiction; Flight -- Fiction; Historical fiction; Inventors -- Fiction; Islands -- Fiction; Prisoners -- Fiction; Ireland -- History -- 1837-1901 -- Juvenile fiction; Ireland -- Fiction; Ireland -- History -- Fiction